GEOGRAPHIC VECTOR OF NATIONAL DEFENSE – LAND POWER - Marjanović, Zoran (Political Review, 2023)
In order to see the influence of the country's foreign policy position, it is necessary to mention at least three elements, the historical events that shaped a particular country, region or continent, the geographical position and the political system of the government. Any of these elements is connected extremely much with geographic or spatial, terrestrial power. All this is related to politics, which is related to the international politics of the state, the region, and global politics. In this research, the elements, primarily geographical, that affect the land power of a state, were analyzed. This research consists of five parts. In the introductory part, it was hinted at what the geographical vector of national defence is and what the influence of land power is on foreign policy positioning. The second part considers the concept of geopolitics and the main representatives of geopolitics as well as their theoretical views on the mutual influence of political, geographical and strategic factors. In the third part, through a critical review of the research of several theoreticians, the strategic thought about the conventional forces of land power was seen. The fourth unit clearly depicts the land power of the countries in whose defence systems the same is strongly expressed. The final part of the paper analyzes what the past brought in the segment of land power, what it represents today and what to expect in the coming period related to the manifestation of the influence of land power on society and states.
Keywords: politics; geography; strategy; geopolitics; land power; conventional forces